The effect of cognitive reappraisal and expression suppression on sadness and the recognition of sad scenes: An event-related potential study - Yan, Chunping; Ding, Qianqian; Wang, Yifei; Wu, Meng; Gao, Tian; Liu, Xintong (Frontiers in Psychology, 2022)
Previous studies have found differences in the cognitive and neural mechanisms between cognitive reappraisal and expression suppression in the regulation of various negative emotions and the recognition of regulated stimuli. However, whether these differences are valid for sadness remains unclear. As such, we investigated the effect of cognitive reappraisal and expression suppression on sadness regulation and the recognition of sad scenes adopting event-related potentials (ERPs). Twenty-eight healthy undergraduate and graduate students took part in this study. In the regulation phase, the participants were asked to down-regulation, expressive suppression, or maintain their sad emotion evoked by the sad images, and then to perform an immediately unexpected recognition task involving the regulated images. The behavioral results show that down-regulation reappraisal significantly diminished subjective feelings of sadness, but expressive suppression did not; both strategies impaired the participants’ recognition of sad images, and expressive suppression had a greater damaging effect on the recognition of sad images than down-regulation reappraisal. The ERP results indicate that reappraisal (from 300 ms to 1500 ms after image onset) and expressive suppression (during 300–600 ms) significantly reduced the late positive potential (LPP) induced by sadness. These findings suggest that down-regulation reappraisal and expression suppression can effectively decrease sadness, and that down-regulation reappraisal (relative to expression suppression) is a more effective regulation strategy for sadness. Both strategies impair the recognition of sad scenes, and expression suppression (compared to down-regulation reappraisal) leads to relatively greater impairment in the recognition of sad scenes.